UMKM GO DIGITAL KAMPUNG BUANTAN LESTARI - Hutabarat, Sakti; Kurnia, Anita; Sinaga, Enjellika; Syahidah, Hafizhah Mardhiatus; Elmi, Imran; Jannah, Miftahul; Faturrahman, Muhammad Ikhsan; Sembiring, Nurfatta Bru; Hutagaol, Princess Restauli; Safitri, Rifda (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2024)
Micro, Small and Medium Enterprises (MSMEs) of Buantan Lestari Village are active business activities both owned by individuals, groups, and business entities that meet the criteria as small and medium enterprises in Buantan Lestari Village. To increase the sales output of MSMEs requires the latest marketing methods. So KUKERTA UNRI students help in introducing digital marketing and providing technological guidance in making e-commerce accounts and how to use e-commerce in digital marketing. The objective of the